Analyses of genome‐scale variation reveal divergence of two Sinalliaria species (Brassicaceae) with continuous but limited gene flow. Issue 3 (23rd October 2018) - Wang, Tian‐Jing; Ru, Da‐Fu; Zhang, Dan; Hu, Quan‐Jun
Abstract: Numerous biogeographic studies have suggested that geographic isolations triggered by Quaternary climatic changes could have contributed greatly to the high species diversity of eastern Asia. However, little is known about how speciation proceeded during the evolutionary divergence of sister species in this region. In this study, we examined genomic divergence and investigated the speciation process of the two species in the genus Sinalliaria endemic to eastern China, S. limprichtiana (Pax) X. F. Jin, Y. Y. Zhou & H. W. Zhang and S. grandifolia (Z. X. An) Huan Hu, com. nov. (Basionym: Alliaria grandifolia Z. X. An (Acta Phytotax. Sin. 23: 396, 1985)). We sequenced the transcriptomes of seven and eight S. limprichtiana and S. grandifolia individuals, respectively. Analysis of transcriptome single nucleotide polymorphism data indicated that both species were well‐delineated with strong genetic differentiation (mean F ST = 0.31). A total of 4000 genes showed differential expression between the two species. Based on these genome‐scale nucleotide variations, we used the allele frequency spectrum for modeling analysis with fastsimcoal to gain insights into the speciation process. Our results suggested divergence with continuous gene flow between the two species. These findings will add to our knowledge on the origin of species diversity in eastern Asia.